Ozone Therapy - A Boon to Dental Sciences - Talukdar Alpana; Kalim Ullah; Rabha Arup Kumar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Ozone therapy has successfully being used in the medical field for the treatment of various diseases for morethan a decade. The versatility of ozone therapy, its unique properties like biocompatibility, antimicrobial,anti-inflammatory, immunostimulant, non-invasive nature, atraumatic, relative absence of side effects oradverse reactions, and better patient compliance were responsible for its widespread dental and medical use.Ozone (O3) is used in dentistry as gas, ozonated water and as ozonated oils. This review of literature is anattempt to summarize its therapeutic potential in dentistry